Electrochemical oxidation of sulfamethazine on a glassy carbon electrode modified with graphene and gold nanoparticles - Cesarino, Ivana [UNESP]; Simoes, Rafael Plana [UNESP]; Lavarda, Francisco Carlos [UNESP]; Batagin-Neto, Augusto [UNESP] (Elsevier B.V., 2016)
This work presents a comprehensive investigation of the oxidation mechanism of sulfamethazine (SMZ) combining electrochemical experiments and molecular modelling techniques. Cyclic voltammetry and differential pulse voltammetry experiments were performed in phosphate buffer solution (PBS) using a glassy carbon (GC) electrode modified with reduced graphene oxide and gold nanoparticles (rGO-AuNPs). Molecular modelling studies were performed via Density Functional Theory (DFT) employing Becke's LYP (B3LYP) exchange-correlation functional and the 6-31G(p,d) basis set. The evaluation of molecular reactivity was accomplished by Condensed-to-Atoms Fukui Indexes (CAFIs). In the theoretical studies, three species were analysed: natural SMZ (SMZ((0))) and its protolytic structures, SMZ((+H)) and SMZ((-H)). The CV results show a well-defined irreversible SMZ oxidation peak at +0.89 V. The molecular modelling studies indicate that SMZ((0)) is the species that effectively participates in the oxidation process. Based on the reactivity indexes obtained, two distinct oxidation mechanisms associated with EC processes occurring in the systems were proposed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Sulfamethazine; Oxidation mechanisms; Electronic structure calculations; Fukui indexes; Density Functional Theory